Evaluation of the Incidence of Mineral Fertilizer Entrapment in Organic Matrix of Residual Biosolids, Cellulose and Sawdust in Maize (Zea mays) Crop - Palacios, Rodrigo Ramírez; Melo, Wanderley José [UNESP]; Rocha, Antonio Mauricio Souza [UNESP]; Araújo, Ademir Sérgio Ferreira; Restrepo-Sánchez, Nora; Jaramillo, Carlos Alberto Peláez (MDPI, 2025)
Sustainable fertilizers are needed to improve nutrient efficiency and reduce environmental impacts. Greenhouse experiments were conducted to evaluate matrix-based organo-mineral fertilizers (OMFs) for Zea mays over 60 days. The study took place during the dry season in Jaboticabal, São Paulo, using 5.5 dm3 plastic pots. Biosolids, deinked paper sludge (cellulose), and sawdust were used as organic matrices. Four treatments (n = 6) were tested: BC (biosolids/cellulose), BS (biosolids/sawdust), FF (uncoated NPK), and NF (no fertilizer). FF received 4.0 g NPK (4-14-8) per pot in two split doses; BC and BS each received 2.0 g NPK entrapped in 2.0 g matrix, applied once at sowing. BC provided the most controlled nutrient release and outperformed FF, increasing plant height by 20.4%, stem diameter by 13.7%, and leaf area by 5.3%. Considering nutrient uptake, BC exceeded FF by 22.5% for N, 38.6% for P, and 22.7% for K while using half the mineral fertilizer. Overall, matrix-based OMFs improved Zea mays growth and nutrient assimilation and may reduce nutrient losses relative to conventional split applications. Because the results derive from a single dry-season greenhouse trial with pots, field-scale validation to the production stage is required to confirm agronomic performance and quantify economic and environmental benefits.